2018
DOI: 10.3758/s13414-017-1478-3
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of peripheral perception of shape with and without saccadic eye movements

Abstract: The cortical representations of a visual object differ radically across saccades. Several studies claim that the visual system adapts the peripheral percept to better match the subsequent foveal view. Recently, Herwig, Weiß, and Schneider (2015, Annals of the New York Academy of Sciences, 1339(1), 97-105) found that the perception of shape demonstrates a saccade-dependent learning effect. Here, we ask whether this learning actually requires saccades. We replicated Herwig et al.'s (2015) study and introduced a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 84 publications
5
36
0
Order By: Relevance
“…The observed modification of size perception was in line with several studies that demonstrated an interaction between the motor adaptation with a distortion of visual localization of the target executed by hand pointing or by perceptual reports (Awater, Burr, Lappe, Morrone, & Goldberg, 2005;Bahcall & Kowler, 1999;Bruno & Morrone, 2007;Collins, Doré-Mazars, & Lappe, 2007;Garaas & Pomplun, 2011;Gremmler, Bosco, Fattori, & Lappe, 2014;Zimmermann & Lappe, 2010). Several more recent studies have indicated that adaptation of visual features can be found without saccadic adaptation (Herwig & Schneider, 2014;Herwig, Weiß, & Schneider, 2015;Herwig, Weiß, & Schneider, 2018;Köller, Poth, & Herwig, 2020;Paeye, Collins, Cavanagh, & Herwig, 2018;Valsecchi & Gegenfurtner, 2016;Valsecchi, Cassanello, Herwig, Rolfs, & Gegenfurtner, 2020). Specifically, features for which this phenomenon occurs are spatial frequency (Herwig & Schneider, 2014;Herwig et al, 2018), shape (Herwig et al, 2015;Köller et al, 2020;Paeye et al, 2018) and size (Bosco et al, 2015;Valsecchi & Gegenfurtner, 2016;Valsecchi et al, 2020).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The observed modification of size perception was in line with several studies that demonstrated an interaction between the motor adaptation with a distortion of visual localization of the target executed by hand pointing or by perceptual reports (Awater, Burr, Lappe, Morrone, & Goldberg, 2005;Bahcall & Kowler, 1999;Bruno & Morrone, 2007;Collins, Doré-Mazars, & Lappe, 2007;Garaas & Pomplun, 2011;Gremmler, Bosco, Fattori, & Lappe, 2014;Zimmermann & Lappe, 2010). Several more recent studies have indicated that adaptation of visual features can be found without saccadic adaptation (Herwig & Schneider, 2014;Herwig, Weiß, & Schneider, 2015;Herwig, Weiß, & Schneider, 2018;Köller, Poth, & Herwig, 2020;Paeye, Collins, Cavanagh, & Herwig, 2018;Valsecchi & Gegenfurtner, 2016;Valsecchi, Cassanello, Herwig, Rolfs, & Gegenfurtner, 2020). Specifically, features for which this phenomenon occurs are spatial frequency (Herwig & Schneider, 2014;Herwig et al, 2018), shape (Herwig et al, 2015;Köller et al, 2020;Paeye et al, 2018) and size (Bosco et al, 2015;Valsecchi & Gegenfurtner, 2016;Valsecchi et al, 2020).…”
Section: Introductionsupporting
confidence: 89%
“…Several more recent studies have indicated that adaptation of visual features can be found without saccadic adaptation (Herwig & Schneider, 2014;Herwig, Weiß, & Schneider, 2015;Herwig, Weiß, & Schneider, 2018;Köller, Poth, & Herwig, 2020;Paeye, Collins, Cavanagh, & Herwig, 2018;Valsecchi & Gegenfurtner, 2016;Valsecchi, Cassanello, Herwig, Rolfs, & Gegenfurtner, 2020). Specifically, features for which this phenomenon occurs are spatial frequency (Herwig & Schneider, 2014;Herwig et al, 2018), shape (Herwig et al, 2015;Köller et al, 2020;Paeye et al, 2018) and size (Bosco et al, 2015;Valsecchi & Gegenfurtner, 2016;Valsecchi et al, 2020). Particular focus has to be given to these two latter studies that tested paradigms able to demonstrate a size recalibration independent of saccade adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…These studies for the most part have involved training and testing during fixation in the absence of eye movements. One exception is the learning of new visual associations between stimuli seen across saccades (40)(41)(42)(43), but in most cases it does not appear that saccades are necessary to elicit this type of learning (39)(40)(41). Other studies have shown that perceptual learning is sensitive to spatiotopic locations defined in part by eye position (44) and that perceptual learning can improve visual sensitivity during saccades (45).…”
Section: Discussionmentioning
confidence: 99%
“…The calibration of peripheral and central perceived appearance is a phenomenon that seems to exist at the boundary of two domains (Herwig, 2015a). On the one hand, it is a perceptual phenomenon, which can be both acquired and expressed without eye movements (Paeye et al, 2018;Valsecchi & Gegenfurtner, 2016). However, this form of calibration should take place most commonly due to trans-saccadic feedback.…”
Section: Introductionmentioning
confidence: 99%